2019
DOI: 10.1111/codi.14818
|View full text |Cite
|
Sign up to set email alerts
|

Functional bowel complaints and quality of life after surgery for colon cancer: prevalence and predictive factors

Abstract: Aim Low anterior resection syndrome (LARS) severely affects the quality of life (QoL) of patients after surgery for rectal cancer. There are very few studies that have investigated LARS-like symptoms and their effect on QoL after colon cancer surgery. The aim of this study was to investigate the prevalence of functional abdominal complaints and related QoL after colon cancer surgery compared with patients with similar complaints after rectal cancer surgery.Method All patients who underwent colorectal cancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 35 publications
2
45
2
Order By: Relevance
“…3 Comorbidity is classified according to a modified the Charlson Comorbidity Index (CCI), excluding cancer. 4 Based on recommendations from the Danish Health Authorities at time of inclusion. Moderate use, 1-14 drinks per week for women and 1-21 drinks per week for men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Comorbidity is classified according to a modified the Charlson Comorbidity Index (CCI), excluding cancer. 4 Based on recommendations from the Danish Health Authorities at time of inclusion. Moderate use, 1-14 drinks per week for women and 1-21 drinks per week for men.…”
Section: Resultsmentioning
confidence: 99%
“…3 Adjusted for 1 + 2+ stage + cancer type. 4 At time of enrollment in the Diet, Cancer and Health Cohort. 5 Based on recommendations from the Danish Health Authorities at time of enrollment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This affected emotional well‐being for some; impatience and frustration accumulated; and the recovery process seemed like an unequal struggle. Likewise, studies investigating patients recovering from colorectal cancer surgery (10, 51) and patients recovering after critical illness (13, 44) to refer to normal life as it was before illness; however, the postoperative recovery process was slow and not comparable to life before surgery (10, 51). For critically ill patients, full recovery was not always achievable due to cognitive or physical impairment, which was hard to accept (13, 44).…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are collectively referred to as the low anterior resection syndrome (LARS), with 40%–50% of patients having long‐term LARS to an extent that it significantly impairs their quality of life 97,98 . In patients undergoing surgery for colon cancer, a recent study showed that 21% suffered from LARS‐like symptoms post‐operatively 99 ; this is a similar proportion to the number of patients reporting a sense of incomplete rectal emptying after sigmoid colectomy 100 …”
Section: Clinical Associationsmentioning
confidence: 99%